Integrating Social Knowledge and Collaboration Tools into Dispersed Product Development - Evans, Richard David; Gao, James Xiaoyu; Martin, Nick; Simmonds, Clive (International journal of advanced corporate learning, 2015)
Employee collaboration and knowledge sharing is vital for manufacturing organisations wishing to be successful in an ever-changing global market place; Product Development (PD) teams, in particular, rely heavily on these activities to generate innovative designs and enhancements to existing product ranges. To this end, the purpose of this paper is to present the results of a validation study carried out during an Engineering Education Scheme project to confirm the benefits of using bespoke Web 2.0-based groupware to improve employee collaboration and knowledge sharing between dispersed PD teams. The results of a cross-sectional survey concluded that employees would welcome greater usage of social computing technologies. The study confirmed that groupware offers the potential to deliver a more effective collaborative and knowledge sharing environment with additional communication channels on offer. Furthermore, a series of recommended guidelines are presented to show how PD teams, operating in globally-dispersed organisations, may use Web 2.0 tools to improve employee collaboration and knowledge sharing.